Regions and economic resilience - Matías Mayor; Paul Ramos (MDPI, 2020)
The term "resilience" originated in environmental studies and describes one's biological capacity to adapt and thrive under adverse environmental conditions. Regional economic resilience is defined as the capacity of a territory's economy to resist and/or recover quickly from external shocks, often even improving on its prior situation (before the shock). The contributions in this book analyse different channels related to processes of mitigation (resistance-recovery) and adaptive resilience (reorientation-renewal), in a wide variety of geographical settings and scales. While the different chapters include relevant methodological advances in this literature, they also obtain relevant results from a policy perspective. Moreover, the wide spectrum of topics and analyses among the contributions in this book extend the current framework, to analyse regional economic resilience, from the intersection of several disciplines involving geographers, economists and demographers, as well as environmental scientists.
Keywords: 330; Coping-Strategie; Regionalökonomik; Nachhaltige Entwicklung